Math, asked by gourabmishra1995, 11 months ago

(4/3x^2yz)×(1/3y^2zx)×(-6xyz^2) multifly the questions ​

Answers

Answered by mysticd
19

 Given \: \Big(\frac{4}{3} x^{2}yz\Big) \times \Big(\frac{1}{3} y^{2}zx\Big) \times </p><p>\Big(-6xyz^{2}\Big)

 = \frac{4}{3} \times \frac{1}{3} \times (-6) \times x^{2} \times x \times x \times y \times y^{2} \times y \times z \times z \times z^{2}

 = \frac{-8}{3} \times x^{2+1+1}\times y^{1+2+1} \times z^{1+1+2}

=  \frac{-8}{3} x^{4}y^{4}z^{4}

Therefore.,

 \red{\Big(\frac{4}{3} x^{2}yz\Big) \times \Big(\frac{1}{3} y^{2}zx\Big) \times </p><p>\Big(-6xyz^{2}\Big)}

 \green{ = \frac{-8}{3} x^{4}y^{4}z^{4}}

•••♪

Answered by Anonymous
30

\bf{\underline{\underline{\bigstar\bigstar\: Solution }}}

\:

 \Big(\frac{4}{3}x^2 yz\Big)×\Big(\frac{1}{3}y^2 zx\Big)×\Big(-6xy z^2\Big)

= \frac{4}{3} \times \frac{1}{3} \times (-6) \times x \times x \times x \times x \times y \times y \times y \times y \times z \times z \times z \times z

= \frac{-24}{9}  \times x^4 \times y^4 \times  z^4

= \frac{-8}{3}  \times x^4 \times y^4 \times  z^4

= \frac{-8}{3}x^4 y^4z^4

Similar questions